Development of the Education Curriculum at Daarul Abroor Modern Islamic Boarding School Banyuasin Regency 1994-2021 - Fatmah; Ria Masmita; Apriana (Criksetra: Jurnal Pendidikan Sejarah, 2023)
This study discusses the development of the educational curriculum at Daarul Abroor Modern Islamic Boarding School in 1994-2021. The research method used in this study is the historical method. The research approach used in this research is a geographic approach, a sociological approach, and an educational approach. The results of this study are as follows (1) Daarul Abroor Modern Islamic Boarding School was founded by K.H. Edy Sunari in 1994 was based on his concern for developing Islamic Education and Da'wah Institutions in Tirtaharja Village. (2) The development of the educational curriculum at the Daarul Abroor Modern Islamic Boarding School in 1994-2021 used the MAK curriculum, Madrasah Aliyah for the Science and Social Sciences Department, Madrasah Aliyah for the Science Department, a combination ofKurikulum 2013and KMI, and KMI. (3) The impact of the development of the Daarul Abroor Islamic Boarding School curriculum for the Daarul Abroor Modern Islamic Boarding School education system, namely in learning activities and extracurricular activities, in addition to the impact on society, namely in the fields of religion, education and the economy.